PARAINFLUENZA VIRUS UPPER RESPIRATORY TRACT ILLNESSES IN PARTIALLY IMMUNE ADULT HUMAN SUBJECTS: A STUDY AT AN ANTARCTIC STATION - PARKINSON, ALAN J.; MUCHMORE, H. G.; SCOTT, L. V.; KALMAKOFF, J.; MILES, J. A. R. (Oxford University Press, 1979)
Outbreaks of respiratory tract illnesses (RTI) in adult humans during October and November 1975 at McMurdo Station, Antarctica, were investigated by viral isolation and serologic procedures. The recovery of viral agents was enhanced by use of cell cultures in the field. Recoveries of parainfluenzaviruses types 1 and 3 and rhinoviruses were made from 10 of 39 nasal washings. Parainfluenzaviruses types 1 and 3 accounted for 50 and 30 percent, respectively, of the total viruses recovered during October and November 1975. Acute and convalescent sera collected from 32 adult humans were examined for antiviral antibody by hemagglutination inhibition (HI) and radioimmunoassay (RIA) techniques. Serologic responses (HI and RIA) confirmed that parainfluenzaviruses were the predominent cause of RTI at McMurdo Station during that time. The temporal relationship between parainfluenzaviral diseases occurring in US communities and at McMurdo suggests that these viruses are transported to the Antarctic by personnel originating within the US. Standardization of the RIA allowed sequential assay of large numbers of sera using multiple preparations of radiolabeled indicator antibody, while ensuring the reproducibility of antiviral antibody titers to within one twofold dilution between subsequent labeled antibody preparations. The RIA detected both lower levels of virus specific antibody and more serologic responses than could be detected by HI.